AN EFFECTIVENESS OF OMEGA 3 SUPPLEMENTATION ON CLINICAL SYMPTOMS IMPROVEMENT AND CLINICAL PARAMETERS OF COVID-19 - Novi Yanti; Lily Indriani Octovia (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2022)
Abstract Background Coronavirus disease 2019 (COVID-19) infection is a disease with high morbidity and mortality rates worldwide. This viral infection can cause metabolic and clinical changes that affect the patient's condition. Omega 3 polyunsaturated fatty acids (ω3-PUFAs) are important mediators of anti-inflammatory and immune response. Thus, it can reduce clinical symptoms of COVID-19 patients. Objective: To know the effect of omega 3 supplementation in improving clinical symptoms and clinical parameters of COVID 19. Methods: Article searches were conducted using advanced searching by combining MesH Terms and abstracts/titles in the Pubmed, Cochrane Library, and Scopus databases. The search found two selected literatures to further conduct a critical assessment. Results:Two articles were selected based on the eligibility criteria and conformity with the Problem Intervention Comparison Outcome (PICO). Study conducted by Sedighiyan et al.,1 showed that there were significant changes in clinical symptoms of COVID-19 patients such as pain, fatigue (p< 0.001), increased appetite (p=0.003), decreased Erythrocyte Sedimentation Rate (ESR) values (p < 0.002), and decreased C-reactive protein (CRP) values ​​(p<0.001). Study conducted by Doaei et al.,2 showed that there was significant decrease in pH (p=0.001), HCO3 (p = 0.001), Be (p = 0.001), and creatinine (p = 0.002), thereby improving clinical symptoms of COVID-19 patients. Conclusion: Omega 3 supplementation can improve clinical symptoms and clinical parameters of COVID 19. However, further research is needed with a larger sample, a longer duration, and with dose adjustment of omega 3 supplementation. Keywords:COVID-19, omega 3 fatty acids, clinical symptoms and clinical parameters improvement